Examining the Coach Motivation Questionnaire in Fitness Professionals (CMQ-FP): Factor Structure, Invariance, and Predictive Analysis. Issue 2 (3rd April 2022) - Rodrigues, F.; Macedo, R.; Mallett, C. J.; Kawabata, M.; Monteiro, D.
ABSTRACT: Purpose : To date, most research on the assessment of motivation has been exerciser-focused and has not considered how fitness professionals' motivations impact their behaviors toward exercisers during training sessions. The purpose of this study was to examine the factor structure of the Coach Motivation Questionnaire in a sample of fitness professionals (CMQ-FP) to ascertain its usefulness for this vocational grouping. Measurement invariance analysis was conducted between female and male fitness professionals, and predictive validity was tested considering need-supportive and need-thwarting behaviors as outcomes. Methods : Participants were 799 fitness professionals (female = 412) aged between 20 and 56 years ( M = 28.71, SD = 3.24), who completed a multi-section survey assessing their motivation toward work and their interpersonal behaviors when engaging with exercisers. Results : The results of this research supported all three hypotheses. First, the hypothesized 6-factor measurement model showed acceptable fit to the data. Second, the factor structure of the CMQ-FP was invariant across gender (male and female fitness professionals). Third, fitness professionals' (autonomous or controlled) motivation was a valid predictor of need-supportive or need-thwarting behaviors. Conclusion : This study supported the factor structure of the CMQ-FP, presenting as a valid measure of motivation in fitness professionals. Understanding fitness professionals' perceptions of their coaching motivation can inform professional development activities to assist fitness professionals to increase understanding of what motivates these professionals and how they might be more need-supportive and less need-thwarting in their pedagogical behaviors.